Non-Communicable Chronic Diseases Among Residents of a Remote Settlement in the Transbaikal Region of the Russian Federation - Oleg Gaisenok (University Library System, University of Pittsburgh, 2019)
Introduction: Over a quarter of the population of the Russian Federation resides in rural communities. However, the data on chronic disease rates in these communities are limited, which makes screening for chronic diseases extremely important. The aim of this study was to measure the prevalence of chronic noncommunicable diseases among residents of a remote settlement in the Transbaikal region, Russian Federation. Methods: A sample of residents from the Transbaikal region settlement was screened in August 2017. The screening included a survey to determine the frequency of self-reported chronic diseases as well as sociodemographic and behavioral risk factors. Additionally, vascular stiffness was measured by volumetric sphygmography using the VaSera-1500 device. Descriptive statistics have been used for data analysis. Results: 126 residents were screened for this study. The prevalence of chronic non-communicable diseases and their risk factors were: hypertension (56.3%), gastrointestinal diseases (33.3%), chronic obstructive pulmonary disease (13.5%), smoking (35.7%), obesity (19.1%), and diabetes mellitus (6.3%). Pathological vascular changes typical of atherosclerosis were found by volumetric sphygmography in 17.5% of cases, with 5.5% of those cases corresponding to significant forms of severe peripheral atherosclerosis (ABI<0.9). An analysis of mortality causes for this settlement for 2016-2017 found that cardiovascular diseases accounted for over 50% of the total number of deaths. Conclusion: This study showed a high prevalence of detectable chronic non-communicable diseases and their associated risk factors. Cardiovascular diseases were the main cause of mortality. Active prevention programs and screenings are required to reduce the burden of chronic diseases in this region.